A Fuzzy Multi-Criteria Decision-Making Approach for Grading of Raw Jute. Issue 5 (4th May 2021) - Das, Subhasis; Ghosh, Anindya
ABSTRACT: Raw jute being a bio-material has a huge level of variability and impreciseness. A scientific method for grading of raw jute considering the underlying impreciseness in jute quality parameters is proposed in this work. The crisp concepts of multi-criteria decision-making are inadequate to model real-life situations. This study proposes a fuzzy multi-criteria group decision-making method that employs the proficiency of three decision-makers to extenuate the fuzziness perceived in quality parameters of raw jute. Strength, defect, root content, color, fineness and bulk density are regarded as criteria for grading of raw jute. Ten raw jute lots are ranked by the intuitionistic multi-criteria multi-expert decision-making method. The ranking of jute lots attained by this method shows a significant agreement with the ranks devised by the technical experts. Hence, the intuitionistic approach emerges as a more profound method for grading of highly heterogenic bio-material like jute.